Bearing estimation of a source with complicated spectrum using a moving sparse antenna array - Korotin, P. I.; Rodionov, A. A.; Turchin, V. I. (Видавництво Національного університету "Львівська політехніка", 2009)
Estimation of bearing of a narrowband source with the use of a sparse equidistant array usually turns out to be ambiguous. For a wideband source with smooth spectrum, this ambiguity can be overcome at the expense of decreasing the spatial resolution. At the same time, the ambiguity of bearing estimate of a narrowband source can be eliminated if the array is moving in respect to the source, and the well-known technique used in radars and sonars with synthetic aperture is used (in this case, a single receiver is enough). In the present paper, a scenario is analyzed when the source spectrum has a smooth wideband component and several narrowband components; such a spectrum is typical, for example, for underwater noise of ships. It is shown that a procedure of aperture synthesis applied to such a signal gives, under some conditions, the same result as conventional beamforming using a motionless array. This fact allows for effective separation of discrete components of the spectrum from its continuous part. Estimates of aperture synthesis duration allowing one to perform such a separation, as well as output signal-to-noise ratios, are presented.
Keywords: аcoustic array systems and processing; aperture synthesis and source localization; sparse antenna array